2017
DOI: 10.1186/s13014-017-0820-1
|View full text |Cite
|
Sign up to set email alerts
|

Institutional analysis of stereotactic body radiotherapy (SBRT) for oligometastatic lymph node metastases

Abstract: BackgroundIn limited metastatic burden of disease, stereotactic body radiotherapy (SBRT) has been shown to achieve high local control rates. It has been hypothesized that SBRT may translate to a better quality of life by delaying the need for systemic chemotherapy and possibly increasing survival. There is limited published literature on the efficacy of SBRT in limited nodal metastases. The primary aim is to review institutional outcomes of patients with solitary or oligometastatic lymph nodes treated with SBR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
28
1
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 28 publications
6
28
1
3
Order By: Relevance
“…Několik studií prokázalo zlepšení přežití pacientů po kompletní resekci retroperitoneálních, intraabdominálních a paraaortálních lymfatických recidiv [22]. Chirurgická resekce takového postižení však bývá technicky náročná a R0 resekce obtížně dosaži- [24,25]. Většina našich pacientů progredovala pouze mimo ozářenou oblast, pokud došlo k lokální progresi v místě ozáření, bylo to vždy spojené s vícečetnou diseminací i mimo ozářený objem.…”
Section: Diskuzeunclassified
See 1 more Smart Citation
“…Několik studií prokázalo zlepšení přežití pacientů po kompletní resekci retroperitoneálních, intraabdominálních a paraaortálních lymfatických recidiv [22]. Chirurgická resekce takového postižení však bývá technicky náročná a R0 resekce obtížně dosaži- [24,25]. Většina našich pacientů progredovala pouze mimo ozářenou oblast, pokud došlo k lokální progresi v místě ozáření, bylo to vždy spojené s vícečetnou diseminací i mimo ozářený objem.…”
Section: Diskuzeunclassified
“…[5,27]. Přibližně pětina oligometastatických pacientů je po lokální léčbě dlouhodobě bez známek onemocnění publikovali Yeung et al [25]. SBRT -extrakraniální stereotaktická radioterapie, GIT -gastrointestinální, Gy -Gray, fr.…”
Section: Diskuzeunclassified
“…Takové oligometastatické onemocnění má lepší prognózu než sys témová diseminace. V těchto případech může být indikována SBRT [90][91][92]. Dáv kování a frakcionace bude významně ovlivněno lokalizací patologické uzliny (obr.…”
Section: Sbrt U Oligometastatického Onemocněníunclassified
“… 28 Yeung et al reported that treatment doses were individualized based on location of tumor in relation to tolerance of nearby organs at risk and that coverage of the Planning Target Volume (PTV) was placed as lowest priority (below dose tolerance of organs at risk). 31 …”
Section: Colorectal Cancermentioning
confidence: 99%